2018
DOI: 10.1021/acs.orglett.8b00931
|View full text |Cite
|
Sign up to set email alerts
|

Stainless Steel-Mediated Hydrogen Generation from Alkanes and Diethyl Ether and Its Application for Arene Reduction

Abstract: Hydrogen gas can be generated from simple alkanes (e.g., n-pentane, n-hexane, etc.) and diethyl ether (EtO) by mechanochemical energy using a planetary ball mill (SUS304, Fritsch Pulverisette 7), and the use of stainless steel balls and vessel is an important factor to generate the hydrogen. The reduction of organic compounds was also accomplished using the in-situ-generated hydrogen. While the use of pentane as the hydrogen source facilitated the reduction of the olefin moieties, the arene reduction could pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 48 publications
(12 reference statements)
0
41
0
4
Order By: Relevance
“…In 2018, an extension of the in situ generated hydrogen approach with SUS304 milling media was reported. [57] This time,milling simple alkanes or diethyl ether in aSUS304 steel milling vessel with balls of the same material led to an increase in pressure inside the milling container.A nalysis of the gaseous mixture by gas chromatography showed the formation of hydrogen and methane upon ball milling. Control experiments using ZrO 2 milling media, diethyl ether, and additives (e.g.F e, Cr, Ni)r evealed, once again, the essential role of chromium metal in favoring the formation of hydrogen.…”
Section: Minireviewsmentioning
confidence: 99%
“…In 2018, an extension of the in situ generated hydrogen approach with SUS304 milling media was reported. [57] This time,milling simple alkanes or diethyl ether in aSUS304 steel milling vessel with balls of the same material led to an increase in pressure inside the milling container.A nalysis of the gaseous mixture by gas chromatography showed the formation of hydrogen and methane upon ball milling. Control experiments using ZrO 2 milling media, diethyl ether, and additives (e.g.F e, Cr, Ni)r evealed, once again, the essential role of chromium metal in favoring the formation of hydrogen.…”
Section: Minireviewsmentioning
confidence: 99%
“…[26] Moreover, they also extended the range of possible metals by using nickel pellets as milling balls,which proved to be an excellent catalyst in the cycloaddition of alkynes yielding cyclooctatetraenes. [27] Other groups picked up the methodology and showed that even stainless steel milling equipment could serve as ac atalyst for hydrogen generation [28] and the reduction of organic compounds. [29] Herein, we demonstrate that milling balls made out of palladium metal (one of the most frequently used transition metal catalysts [30] )c atalyze the Suzuki cross-coupling reaction.…”
mentioning
confidence: 99%
“…Alkene and alkyne bonds and nitro, azido, and keto groups were reduced in 62-100% yield by in situ hydrogen generation ( Figure 5). Furthermore with SUS304 steel vials as catalyst, alkanes and Et 2 O were used as hydrogen sources for hydrogenation of aromatic compounds, alkenes, alkynes, and ketones [33].…”
Section: Synthesismentioning
confidence: 99%